Measuring Client Satisfaction Level From Migration Manual Reconciliations system to Automatic Reconciliations system In Bank Danamon Indonesia Using Kano Model - Rizaldi, Rizaldi (Swiss German University, 2019)
In banking industry, reconciliation software can help you rise to a range of regulatory, business and operational challenges. In this new, challenging operational environment, an automated reconciliation strategy has proved to be a mandatory system to help reduce costs and risk, to achieve compliance and improve transparency, efficiency and scalability. But migrating system is a big project, And like other big projects, sometimes the result are not satisfactory, to measure client satisfaction on this project, we use Kano Model to measure it, a theory of customer satisfaction and product development developed by Professor Noriako Kano in 1980.